The Absorption of Islamic Law in Indonesia in the Field of Ethics - Muin, Rahmawati; Samin, Sabri; Sari, Andi Enri Erna; Taqiyuddin BN, Andi Muh. (Formosa Journal of Sustainable Research, 2024)
The purpose of this research is to reveal the Regulation/Theory of Islamic Law in Indonesia in the Field of Ethics and the Practice of Islamic Law in Indonesia in the Field of Ethics. This research is qualitative research, the type of research is library research. The data collection method used is literature study. The results showed that; 1) The validity of Islamic Law in Indonesia in the Field of Ethics, can be seen from the legality of ethics applied in the form of regulations or official rules and of course in general it can be understood that the ethics of association, markets, business, clothing, and professions are in line with Islamic law, although there are rules that need to be discussed. 2) The implementation of Islamic Law in Indonesia in the field of ethics can be seen from the existing cases. Because the existence of a case related to ethical violations, both socialization, markets, business, clothing, and professions, shows that the rules or regulations that contain these ethics really exist and are applied. As for the application, it cannot be said to be maximized, with the presence of cases of ethical violations. cases of ethical violations